Analisis Stabilitas Sistem Keuangan dan Faktor-Faktor yang Mempengaruhinya - Febyana Dewi Cahyani; Nugroho Sumarjiyanto Benedictus Maria (Universitas Diponegoro, 2023)
This study aims to examine the factors influencing the stability of the financial system. It employs a quantitative research approach, utilizing secondary data sources. The analysis is conducted using multiple linear regression, with inflation as the dependent variable and the money supply, interest rates, and exchange rates as independent variables. The analysis covers the period from January 2020 to December 2022. The results indicate that both the money supply and interest rates have a significant positive effect on inflation.